162k views
2 votes
PLEASE HELP ME! THANK YOUU!

PLEASE HELP ME! THANK YOUU!-example-1
User Rnwood
by
5.9k points

2 Answers

3 votes

3/4

Explanation:

Rate of change = (f(-4)-f(0))/-4

Plug in the numbers

f(-4) = 10 - (3/4)(-4) = 10-3 = 7

f(0) = 10 - (3/4)(0) = 10

Plug back into first equation

(7-10) = 3/4

-4

User Gkiely
by
5.9k points
3 votes

9514 1404 393

Answer:

-3/4

Explanation:

The given function is a linear function with a slope of -3/4. (The slope is the coefficient of x.) The slope is the rate of change. For a linear function, the slope is the same everywhere. That is, the "average rate of change" and the "rate of change" and the "slope" are all the same value.

Here, the average rate of change is -3/4.

__

Alternate solution

You can compute the average rate of change using the formula ...

average rate of change = (f(x2) -f(x1))/(x2 -x1)

For x1 = -4 and x2 = 0, we need to know the function values:

f(-4) = 10 -(3/4)(-4) = 13

f(0) = 10 -(3/4)(0) = 10

So, the average rate of change formula gives ...

average rate of change = (10 -13)/(0 -(-4)) = -3/4

The average rate of change is -3/4.

PLEASE HELP ME! THANK YOUU!-example-1
User Greg Sexton
by
7.4k points